Suboptimal Assessment of Interunit Task Interdependence: Modes of Integration and Information Processing for Coordination Performance - Sherman, J. Daniel; Keller, Robert T. (Organization Science, 2011)
This investigation extends previous research on cross-functional integration. Building on earlier theoretical development, a graduated sequence of modes of integration is tested in relation to interunit task interdependence in a global logistics support organization. This research addresses the question of what effects are associated with perceptual error in the assessment of interunit task interdependence. The results demonstrate that as the deviation between perceived and latent interdependence increases, the deviation between optimal and observed integration modes increases. These deviations are found to occur in over 30% of the cases. In addition, this research addresses the question of what effects are associated with the suboptimal implementation of modes of integration. The results demonstrate that as the deviation between optimal and observed integration modes increases, coordination performance decreases. The implications for theory and practice of improved coordination performance and information processing theory are discussed.